DEEP VEIN ARTERIALISATION - Cvetanovski, Vlatko; Arsovski, Andreja; Mitevski, Aleksandar; Cvetanovska, Marija; Kondov, Borislav; Dimitrov, Zoran (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Critical lower limb ischemia in the absence of distal arterial circulation presents an urgent situation, which must be treated immediately if we want to save the foot or limb from amputation. According to Fountain these patients are classified in Class III or in Class IV. Approximately 14%â€“20% of patients with critical lower limb ischemia are unsuited for distal arterial reconstruction and face major distal amputation. Some patients with critical limb or foot ischemia will achieve wound healing with conservative therapy, it is impossible to predict who these patients will be, and it is therefore recommended that revascularization remains an important first-line treatment. We present our first clinical case of arterialization of deep posterior tibial vein in treatment of critical ischemia of the foot. Arterialization of the veins in properly selected patients can prevent major amputation in patients with critical limb ischemia where no other treatment option could be performed. Key words : arterialization of vein, deep vein, deep vein arterialization, critical limb ischemia https://doi.org/10.55302/JMS2141061c